2005
DOI: 10.1097/01.rct.0000171913.74086.1b
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Weighted Imaging of Malignant Breast Tumors

Abstract: The authors used breast diffusion-weighted imaging (DWI) to diagnose breast cancer and identify cancer extension. Isotropic DWI was performed with EPI. The apparent diffusion coefficient (ADC) value was calculated and displayed on an ADC map. The authors compared between the distribution of low ADC values and pathologic cancer extension. The mean ADC value of breast cancer was 1.12 +/- 0.24 x 10(-3) mm/s, which was lower than that of normal breast tissue. The ADC value for invasive ductal carcinoma was lower t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
62
2
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 283 publications
(69 citation statements)
references
References 18 publications
4
62
2
1
Order By: Relevance
“…A decrease in the ADC is expected with increased intracellular tissue caused either by cell swelling or increased cellular density rather than vascular perfusion. HER2-positive expression had a more malignant phenotype accompanied by cell proliferation, invasion and metastasis [1,2,8]. However, in our study, no statistically significant difference was observed between the negative and positive group of IDC NOS.…”
Section: Discussioncontrasting
confidence: 51%
See 4 more Smart Citations
“…A decrease in the ADC is expected with increased intracellular tissue caused either by cell swelling or increased cellular density rather than vascular perfusion. HER2-positive expression had a more malignant phenotype accompanied by cell proliferation, invasion and metastasis [1,2,8]. However, in our study, no statistically significant difference was observed between the negative and positive group of IDC NOS.…”
Section: Discussioncontrasting
confidence: 51%
“…In vivo, the ADC value is affected not only by microscopic motion from diffusion but also perfusion. The perfusion effect would cause significantly greater artificially increased ADC in malignant lesions owing to increasing microvessel count of tumour angiogenesis [1,2,22,28]. According to several studies, the ADC value was significantly lower in malignant than in benign lesions, indicating that this effect might be mainly owing to the effect of high cell density overcoming the opposite effects of perfusion [1,5,14].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations